The effect of two different calcium antagonists on the glomerular haemodynamics in the dog - Heller, J; Horácek, V (Pflugers Archiv, 1990)
Kidney function of beagles fed a constant amount of food containing 3 mmol sodium.kgbodywt-1.day-1, and anaesthetized with pentobarbitone was investigated by clearance and micropuncture techniques during an intrarenal infusion of saline or the calcium antagonists verapamil (VER, 4 micrograms.kgbodywt-1.min-1) or nifedipine (NIF, 0.3 microgram.kgbodywt-1.min-1). Neither drug changed the mean arterial pressure. Apart from the natriuresis and diuresis, which were significantly greater with NIF than with VER, the response to both drugs was similar. Increases in renal blood flow (RBF; 17% with VER, 20% with NIF), glomerular filtration rate (GFR; VER: 34%; NIF: 39%) and filtration fraction (VER: 12%; NIF: 14%) were observed; similar values were obtained at the single nephron level. Pressure in glomerular capillaries, measured directly after ablation of a thin layer of cortex corticis, was increased by 11% with VER and 10% with NIF; no changes in proximal tubular and peritubular capillary pressure were seen. The glomerular ultrafiltration coefficient (Kf) did not change with either drug. Total arteriolar resistance was decreased (VER: 20%; NIF: 15%) due to a decrease in afferent resistance (VER: 31%; NIF: 27%) with no corresponding change in efferent resistance. The cause of the lack of responsiveness of the efferent arteriole remains unclear. In conclusion, in acute experiments with intrarenal administration, both drugs increase RBF and GFR by a preferential afferent dilatory mechanism without any change in Kf.
Keywords: psi; nifedipin; Vascular Resistance; moč; Dogs; Punctures; verapamil; Nifedipine; Female; blokátory kalciových kanálů; Verapamil; zvířata; osmolární koncentrace; cévní rezistence; Calcium Channel Blockers; Urine; ženské pohlaví; Male; Kidney Glomerulus; punkce; Animals; hemodynamika; mužské pohlaví; Hemodynamics; Osmolar Concentration; glomerulus